Introduction - Vaz Stein, Anderson Leonardo (Romanitas - Revista de Estudos Grecolatinos, 2026)
This dossier presents readers with new historiographical contributions that position non-Roman peoples as the protagonists of profound political and social transformations, characterized by both continuities and ruptures that led to the reorganization of the Western Mediterranean.
Keywords: Late Antiquity; Romans and Barbarians; Continuity and Rupture; Political and Cultural Negotiation; Western Mediterranean